2020
DOI: 10.1016/j.jaim.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective potential of Myrica esulenta in Haloperidol induced Parkinson’s disease

Abstract: Background Myrica esculenta is a notable therapeutic plant widely utilized in Indian system of medicine. Ayurvedic literature reported fruit and bark of this plant is used in gulma, jvara, arsa, grahani, pandu roga, hrillasa, mukha roga, kasa, svasa, agnimandhya, aruchi, meha , and kantharoga . Objective The present study aimed to investigate the neuroprotective potential of “Himalayan Bayberry” ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…(Trevitt et al., 2009; Maj et al., 1990; Juszkiewicz et al., 1994; Juszkiewicz et al., 1995; Mandhane et al., 1997; Konieczny et al., 1999; Jagtap & Inamdar, 2001; Ossowska et al., 2001; Breysse et al., 2002; Moo‐Puc et al., 2003; Ossowska et al., 2003; Rukoyatkina et al., 2003; Wardas et al., 2003; Tanganelli et al., 2004; Ossowska et al., 2005; Zazpe et al., 2006; Lopez et al., 2007; Sibille et al., 2007; Ahemad et al., 2009; Beurrier et al., 2009; Góngora‐Alfaro et al., 2009; Konieczny et al., 2009; Ardashov et al., 2011; Joshi et al., 2011; Trevizol et al., 2011; Lopez et al., 2012; Shyamjith et al., 2012; Goudet et al., 2012; Acuña‐Lizama et al., 2013; Konieczny & Lenda, 2013; Atack et al., 2014; Ittiyavira & Ruby, 2014; Azam, et al., 2009; Zheng et al., 2014; Gmiro et al., 2015; Maurice et al., 2015; Nade et al., 2015; Bhangale & Acharya, 2016; Dhingra & Gahalain, 2016; Basu et al., 2017; Chitra et al., 2017; Gupta et al., 2017; Kumari et al., 2017; Kronbauer et al., 2017; Tian et al., 2017; Yang et al., 2016; Engelhardt et al., 2018; Slee et al., 2008; Saleem et al., 2019; Kabra et al., 2020; Łażewska et al., 2020; Chiu et al., 1981; Schmidt & Bubser, 1989; Schmidt et al., 1991; Kretschmer, 1994; Kretschmer et al.,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Trevitt et al., 2009; Maj et al., 1990; Juszkiewicz et al., 1994; Juszkiewicz et al., 1995; Mandhane et al., 1997; Konieczny et al., 1999; Jagtap & Inamdar, 2001; Ossowska et al., 2001; Breysse et al., 2002; Moo‐Puc et al., 2003; Ossowska et al., 2003; Rukoyatkina et al., 2003; Wardas et al., 2003; Tanganelli et al., 2004; Ossowska et al., 2005; Zazpe et al., 2006; Lopez et al., 2007; Sibille et al., 2007; Ahemad et al., 2009; Beurrier et al., 2009; Góngora‐Alfaro et al., 2009; Konieczny et al., 2009; Ardashov et al., 2011; Joshi et al., 2011; Trevizol et al., 2011; Lopez et al., 2012; Shyamjith et al., 2012; Goudet et al., 2012; Acuña‐Lizama et al., 2013; Konieczny & Lenda, 2013; Atack et al., 2014; Ittiyavira & Ruby, 2014; Azam, et al., 2009; Zheng et al., 2014; Gmiro et al., 2015; Maurice et al., 2015; Nade et al., 2015; Bhangale & Acharya, 2016; Dhingra & Gahalain, 2016; Basu et al., 2017; Chitra et al., 2017; Gupta et al., 2017; Kumari et al., 2017; Kronbauer et al., 2017; Tian et al., 2017; Yang et al., 2016; Engelhardt et al., 2018; Slee et al., 2008; Saleem et al., 2019; Kabra et al., 2020; Łażewska et al., 2020; Chiu et al., 1981; Schmidt & Bubser, 1989; Schmidt et al., 1991; Kretschmer, 1994; Kretschmer et al.,…”
Section: Resultsmentioning
confidence: 99%
“…The variation in publications per year is important data. As noted, the haloperidol‐induced catalepsy model for parkinsonism was first applied in the early 1980s (Chiu et al., 1981; Pycock et al., 1982; Schallert & Teitelbaum, 1981; Scheel‐Krüger & Magelund, 1981) and is still widely used nowadays (Bhattamisra et al., 2020; Chaudhary & Dhande, 2020; Kabra et al., 2020; Łażewska et al., 2020; Olaya et al., 2020; Parambi et al., 2020; Pardo et al., 2020; Sanawar et al., 2020; Sharma et al., 2020; Sita et al., 2020). In fact, since 2000, the number of articles published using this model has increased and become more constant (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of haloperidol is associated with the blockade of dopamine receptors, central alphaadrenoblocking action and disruption of the process of reverse neuronal capture and deposition of adrenaline. Unfortunately, the use of haloperidol is limited by the side effects of the drug, in particular extrapyramidal disorders (Kabra et al 2020).…”
Section: Experimental Modelmentioning
confidence: 99%
“… 18 Different studies have revealed that haloperidol-induced catalepsy presents a robust model to investigate the anti-parkinsonian activity. 19 However, other chemicals like rotenone and paraquat were also used to induce the PD, 20 but in this study, haloperidol is used for the Parkinsonism model. The advantage of haloperidol-induced parkinsonism is that haloperidol blocks the D 2 receptors and causes the depletion of dopamine.…”
Section: Introductionmentioning
confidence: 98%
“…Haloperidol is an antipsychotic drug used for the treatment of schizophrenia by blocking the dopamine receptors and increasing its metabolism, resulting in the generation of hydrogen peroxide and ROS, and hence causing neurotoxicity and oxidative stress . Different studies have revealed that haloperidol-induced catalepsy presents a robust model to investigate the anti-parkinsonian activity . However, other chemicals like rotenone and paraquat were also used to induce the PD, but in this study, haloperidol is used for the Parkinsonism model.…”
Section: Introductionmentioning
confidence: 99%